Emotional distress and affective knowledge representation one year after the COVID-19 outbreak - Laura Barca; Pierpaolo Iodice; Amine Chaigneau; GianLuca Lancia; Giovanni Pezzulo (PLoS ONE, 2025)
This study examines whether the detrimental effects of the COVID-19 pandemic on the affectivity of the population extend one year after the outbreak. In an online-mobile session, participants completed surveys (i.e., demographic characteristics, positive-negative affectivity, interoceptive awareness) and a similarity judgment task of triplets of emotional concepts, from which we derived 2D maps of their affective knowledge representation. Compared with pre-pandemic data derived from a comparable population, we report three main findings. First, we observed enhanced negative affectivity during the pandemic, but no changes in positive affectivity levels. Second, increased self-reported interoceptive awareness compared to pre-pandemic data, with greater attention to bodily sensations and adaptive aspects of interoceptive sensitivity. Furthermore, female participants reported higher scores than males on the questionnaire subscales of Emotional Awareness and Attention Regulation. Third, the effect of pandemic-related conditions is also apparent in the mental organization of emotional concepts, especially for female participants (i.e., reduced coherence in the organization of the concepts along the arousal dimension and more misclassification of concepts based on arousal) and participants who did not perform physical activity (a collapse of the arousal dimension). Some of the effects of the pandemic, thus, persist about a year after the outbreak. These results advise providing programs of psychological and emotional assistance throughout the pandemic beyond the outbreak, and that age-dependent gender differences should be accounted for to define tailored interventions. Physical activity might relieve pandemic-related stressors, so it should be promoted during particularly stressful periods for the population.